Organic acids in the rhizosphere and root characteristics of soybean (Glycine max) and cowpea (Vigna unguiculata) in relation to phosphorus uptake in poor savanna soils - Nwoke, O.C.; Diels, J.; Abaidoo, Robert C.; Nziguheba, Generose; Merckx, Roel (2008)
Root characteristics associated with phosphorus (P) uptake under limiting soil-P conditions were examined in two sets of greenhouse experiments. Average diameter and length of soybean, cowpea, maize and sorghum roots were assessed after 7 weeks in three low-P soils amended with P fertilizer at 0, 3, 6, 11 and 23 mg Pkg. Organic acids in the rhizosphere of soybean, cowpea and pigeon pea were separately evaluated in one soil amended with or without rock phosphate, iron phosphate, aluminium phosphate, calcium phosphate, or triple super phosphate. Unplanted soil served as the control. The growth of soybean, cowpea, maize, and sorghum was significantly improved with P application in all the soils and the amount of P applied played an important role. The shoot dry matter yield and P accumulation correlated significantly with the root length of cowpea and the average diameter of sorghum roots. Citric acid was the only organic acid detected in measurable quantities in the rhizosphere of all plants tested; on average, it varied from 4 (pigeon pea) to 17 (soybean) ìmolg soil. For soybean, the secretion of citric acid appeared important for P acquisition in P-limiting environments whereas for cowpea, the size of the roots may be more important.